2021
DOI: 10.1371/journal.ppat.1009859
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics provide new insights into mechanisms of Wolbachia-induced paternal defects in Drosophila melanogaster

Abstract: Wolbachia is a group of intracellular symbiotic bacteria that widely infect arthropods and nematodes. Wolbachia infection can regulate host reproduction with the most common phenotype in insects being cytoplasmic incompatibility (CI), which results in embryonic lethality when uninfected eggs fertilized with sperms from infected males. This suggests that CI-induced defects are mainly in paternal side. However, whether Wolbachia-induced metabolic changes play a role in the mechanism of paternal-linked defects in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 66 publications
1
9
0
Order By: Relevance
“…In the present study, we identified 643 DEPs, and again, most (72.78%) were downregulated due to Wolbachia infection. Among those significantly changed proteins, many of them are involved in metabolic processes, which is similar to the results observed in our previous study [ 20 , 31 ] and reports from other groups [ 32 , 33 ]. In studies on human, mouse, boar, and rainbow trout sperm proteome, many sperm proteins were also related to the metabolic processes [ 34 , 35 , 36 , 37 ].…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, we identified 643 DEPs, and again, most (72.78%) were downregulated due to Wolbachia infection. Among those significantly changed proteins, many of them are involved in metabolic processes, which is similar to the results observed in our previous study [ 20 , 31 ] and reports from other groups [ 32 , 33 ]. In studies on human, mouse, boar, and rainbow trout sperm proteome, many sperm proteins were also related to the metabolic processes [ 34 , 35 , 36 , 37 ].…”
Section: Discussionsupporting
confidence: 91%
“…Aspartate transporters contain a large number of proteins, including SLC1A1, SLC1A2, SLC1A3, SLC1A6, SLC1A7, SLC25A12, SLC25A13,SLC38A7, and SLC38A8 [33,34]. To To further investigate the impact of viral infection on aspartate uptake, we detected the aspartate uptake during infection using 13 C-labeled aspartate. The results showed that the level of 13 C-aspartate was significantly enhanced in FMDV-, EV71-, or SVV-infected cells compared to mock-infected cells (Fig 6F ), suggesting that FMDV, EV71, and SVV infection promoted aspartate uptake.…”
Section: Fmdv Infection Enhanced the Protein Expression Of Slc38a8mentioning
confidence: 99%
“…To further determine the impact of SLC38A8 on FMDV-, EV71-, and SVV-induced aspartate uptake, 13 C-labeled aspartate uptake in WT and SLC38A8 -/cells was assessed during viral infection. There was no change in 13 C-labeled aspartate level in mock-infected WT and SLC38A8 -/cells, while the level of 13 C-labeled aspartate was significantly decreased in FMDV-, EV71-, or SVV-infected SLC38A8 -/cells compared to that of FMDV-, EV71-, or SVV-infected WT cells (Fig 7D).…”
Section: Slc38a8 Was Responsible For Fmdv-induced Aspartate In Vitromentioning
confidence: 99%
See 2 more Smart Citations